Answer:
see explanation
Step-by-step explanation:
The average rate of change over the closed interval [ a, b ] is
[tex]\frac{f(b)-f(a)}{b-a}[/tex]
here [ a, b ] = [ 0, 8 ]
f(b) = f(8) = [tex]\frac{16-2}{40-6}[/tex] = [tex]\frac{14}{34}[/tex] = [tex]\frac{7}{17}[/tex]
f(a) = f(0) = [tex]\frac{-2}{-6}[/tex] = [tex]\frac{1}{3}[/tex]
f(b) - f(a) = [tex]\frac{7}{17}[/tex] - [tex]\frac{1}{3}[/tex] = [tex]\frac{4}{51}[/tex]
average rate of change = [tex]\frac{\frac{4}{51} }{8}[/tex] = [tex]\frac{1}{102}[/tex]